Three-dimensional pituitary gland volume on MRI - A normative study - Rahman, Md Towhidur; Sharif, Md Mofazzal; Mohiuddin, AS (KYAMC Journal, 2018)
Background: Standard reference values for the pituitary gland volume of healthy Bangladeshi is necessary to facilitate assessment and diagnosis of pituitary pathology. Objectives: To obtain the dimensions of normal pituitary gland using T1-weighted magnetic resonance images (MRI) and to determine their relationship with age, sex. Materials & Methods: MRI of 100 individuals with clinically normal pituitary function (age range 14- 82 years) was taken in order to obtain volumetric measurements of the pituitary gland. The data obtained were stratified based on age and sex for analysis. Results: The mean pituitary gland volumes were 332.1 ± 146.8 mm3 and 324.2 ± 130.2 mm3 while the mean pituitary heights were 6.22 ± 1.6 mm and 6.42 ± 1.57 mm in males and females, respectively. Although there was no statistically significant difference between pituitary height and pituitary volume in both sexes, they correlated negatively with increasing age (r = -202, P = 0.04 and r = -410, P = 0.000, respectively). The mean pituitary widths (9.03 ± 2.48 mm and 9.21 ± 1.84 mm) and depths (10.5 ± 1.6 mm and 10.42 ± 1.52 mm) in males and females, respectively, did not show remarkable changes with age and sex in the individuals studied. Statistical tests applied included Student's t-test and Pearson correlation. A minimum level of statistical significance was set at P < 0.05. Conclusion: With this study, we have provided reference values in Bangladeshi population for the dimensions of normal pituitary gland. KYAMC Journal Vol. 9, No.-2, July 2018, Page 53-55